A Measure of Illness Awareness in Individuals With Nicotine Dependence—Nicotine Use Awareness and Insight Scale. Issue 4 (12th November 2021) - Kim, Julia; Kambari, Yasaman; Taggar, Anmol; Quilty, Lena C; Selby, Peter; Caravaggio, Fernando; Ueno, Fumihiko; Song, Jianmeng; Pollock, Bruce G; Graff-Guerrero, Ariel; Gerretsen, Philip
Abstract: Introduction: Impaired illness awareness or the inability to recognize that one has a dependence on nicotine may be a major barrier to seeking cessation treatment. To better understand the role of impaired illness awareness on treatment-seeking behavior and clinical outcomes, we developed and examined the psychometric properties of a novel scale measuring illness awareness in individuals with dependence on nicotine. Aims and Methods: We developed the Nicotine Use Awareness and Insight Scale (NAS), a 7-item self-report measure to assess the theoretical construct of illness awareness in individuals with dependence on nicotine (www.illnessawarenessscales.com ). Data from participants 18 years of age or older were collected via a web-based survey company, Dynata. Participants with moderate dependence on nicotine were included, defined by a score of four or more on the Fagerström Test for Cigarette Dependence (FTCD) or the FTCD adapted for electronic cigarettes (eFTCD). Results: A total of 100 participants (mean [SD] age = 49.1 [16.1] years, 52% women) that met the inclusion criteria for either FTCD ( n = 50) or eFTCD ( n = 50) were included. The NAS demonstrated good convergent ( r = .74, p < .001) and discriminant validity ( r = .03, p = .786). It also demonstrated good internal consistency (Cronbach's alpha = 0.78) and one-month test-retest reliability (intra-class correlation = 0.86). An exploratory factor analysis yielded the retention of two components. Conclusions: The NAS is a novel scale to asses illness awareness in individuals with dependence on nicotine. This study provides initial support for the psychometric validity and reliability of NAS. Implications: The NAS may be used in research and clinical practice to evaluate the impact of impaired illness awareness on treatment-seeking behavior and clinical outcomes.